1996
DOI: 10.3171/jns.1996.85.5.0853
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive craniectomy in a rat model of “malignant” cerebral hemispheric stroke: experimental support for an aggressive therapeutic approach

Abstract: Acute ischemia in the complete territory of the carotid artery may lead to massive cerebral edema with raised intracranial pressure and progression to coma and death due to uncal, cingulate, or tonsillar herniation. Although clinical data suggest that patients benefit from undergoing decompressive surgery for acute ischemia, little data about the effect of this procedure on experimental ischemia are available. In this article the authors present results of an experimental study on the effects of decompressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(47 citation statements)
references
References 36 publications
2
43
0
2
Order By: Relevance
“…Following DC and dura opening, the edematous brain may herniate through the craniectomy opening rather than through the tentorial incisura, which prevents brainstem compression (7,8). More sufficient decompression and suitable ICP decreases may be achieved if this extracalvarial movement is bilateral.…”
Section: Discussionmentioning
confidence: 99%
“…Following DC and dura opening, the edematous brain may herniate through the craniectomy opening rather than through the tentorial incisura, which prevents brainstem compression (7,8). More sufficient decompression and suitable ICP decreases may be achieved if this extracalvarial movement is bilateral.…”
Section: Discussionmentioning
confidence: 99%
“…[6,26] It is widely accepted that DS should not be postponed so long that irreversible brainstem changes, such as Duret hemorrhages, occur. [17] However, the optimal time at which DS should be performed remains debatable.…”
Section: Discussion Causes Of Pupillary Dilation In Patients Withmentioning
confidence: 99%
“…According to the EBIC and the American Brain Injury Consortium (ABIC) guidelines for SHI, [12,15] DS is one therapeutic option for brain edema that does not respond to conventional therapeutic measures such as hyperventilation, osmotherapy with mannitol, ventricular drainage of CSF, and metabolic suppression therapy. [12,[16][17][18][19][20] However, specific indications and timing for this intervention have not been standardized as yet. It has been reported that the indications for DS in patients with SHI are the appearance of diffuse unilateral or bilateral brain swelling with correlating clinical deterioration; worsening of GCS score and/or dilation of pupils unresponsive to light; therapy-resistant increase in ICP to >30 mmHg and/or a reduction in CPP to <45 mmHg; and initial GCS score of ≥4 and a GCS score of at least 4 on the 1st posttraumatic day.…”
Section: Discussion Causes Of Pupillary Dilation In Patients Withmentioning
confidence: 99%
“…9 In recent years, both animal and clinical studies reported beneficial effects of DC for treating conditions, such as traumatic brain injury 10,11 and malignant middle cerebral artery (MCA) infarction. 12,13 With respect to SAH, however, relatively few studies have been published regarding the application of DC and its effect on outcome; moreover, the results published to date are contradictory and controversial. [14][15][16][17][18] To address these questions, we performed DC to evaluate the role of SAH-induced elevated ICP and subsequent global ischemia and to investigate whether DC may serve as a therapeutic option for SAH using a standardized animal model.…”
mentioning
confidence: 99%